DESTRUCTING THE ISLAMIST IN INDONESIA: Joko Widodo Policy and Its Controversy - Hasbi Aswar (Hasanuddin University, 2018)
The tension between the Islamist group and the state has risen in Indonesia this 2017. In the mid of 2017, Joko Widodo (Jokowi) government has announced to disbandHizbut Tahrir Indonesia (HTI) as one of the Islamist groups in Indonesia. It happened in the midst of protest toward Jokowi for his ignorance to respond the alleged religious defamation by Ahok, governor of Jakarta. This article explores the discourse used by Jokowi government and its allies to ban HTI in Indonesia. It also explains the reason for the policy produced and political interests behind it. This paper argues that the dissolution of HTI is by no means for legal and security reason but for political interest of Joko Widodo and his political allies.